Indoor environment propagation review - Obeidat, H.; Alabdullah, A.; Elkhazmi, E.; Suhaib, W.; Obeidat, O.; Alkhambashi, M.; Mosleh, M.; Ali, N.; Dama, Y.; Abidin, Z.; Abd-Alhameed, R.; Excell, P. (Elsevier, 2020)
A survey of indoor propagation characteristics is presented, including different models for path loss, shadowing and fast fading mechanisms, different channel parameters including signal strength, power delay, coherence bandwidth, Doppler spread and angle of arrival. The concepts of MIMO channels are also covered. The study also explores many types of deterministic channel modelling, such as Finite Difference Time Domain, Finite Integration Method, Ray tracing and the Dominant path model. Electromagnetic properties of building materials, including frequency dependence, are also investigated and several models for propagation through buildings are reviewed.